Implementasi Simple Additive Weighting Dalam Sistem Rekomendasi Beasiswa di SMK Tarbiyatul Ulum Karawang - Yusup Mad Cani; Hannie Hannie; Azhari Ali Ridha (Jurnal Teknologi Informasi dan Multimedia, 2023)
Scholarships are a program that students get to continue their studies. Tarbiyatul Ulum Vocational School is a formal secondary level vocational institution which has a large number of students. Some of these students are entitled to get scholarships available at Tarbiyatul Ulum Vocational School. So far, the Administrative Staff to select students who are entitled to receive scholarships is done manually so that it takes a long time and the possibility of human error occurs so it is not efficient to use in selecting students who will get scholarships with a large number of students. Therefore, a scholarship recommendation system is needed that can provide consideration to Administrative Staff in grouping students based on scholarships that are suitable for them to participate in, so that with this recommendation system Administrative Staff can clearly group students without the occurrence of human error because it has been calculated automatically by the system. The system uses the Simple Additive Weighting method as a decision-making method with various criteria with weighted values according to the existing criteria and the Waterfall method as a method for making the system starting from the planning stage to the maintenance stage so that it is sequential in the development of this recommendation system. The results of this system can directly recommend selected students for the relevant scholarship based on the highest recommendation value which is calculated using the Simple Additive Weighting method.